2021
DOI: 10.1186/s12904-021-00726-1
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care nurse champions’ views on their role and impact: a qualitative interview study among hospital and home care nurses

Abstract: Background One of the strategies to promote the quality of palliative care in non-specialised settings is the appointment of palliative care nurse champions. It is unclear what the most effective model to implement the concept of nurse champions is and little is known about palliative care nurse champions’ own views on their role and responsibilities. This paper aims to describe views of palliative care nurse champions in hospitals and home care on their role, responsibilities and added value. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
3
8
0
1
Order By: Relevance
“…In contrast, the results indicated that heavy workload caused the resource nurse role to be underutilized. This is consistent with Engel et al [ 4 ], who reported that trained nurse champions in palliative care are able and willing to contribute to a greater extent in competence activities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, the results indicated that heavy workload caused the resource nurse role to be underutilized. This is consistent with Engel et al [ 4 ], who reported that trained nurse champions in palliative care are able and willing to contribute to a greater extent in competence activities.…”
Section: Discussionsupporting
confidence: 92%
“…The term resource nurse or the parallel term link nurse or nurse champion denotes a healthcare role that is established internationally and is used in a wide area of clinical settings such as infection prevention and control [ 1 ], wound and skin care [ 2 ], diabetes care [ 3 ] and palliative care [ 4 , 5 ]. However, neither the resource nurses’ role nor the similar terms are distinctively defined [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of respondents was classified according to the Australian Statistical Geographical Classification -Remoteness Area 2016. 7 The 152 respondents came from Queensland (n=79), Western Australia (19), South Australia (16), Victoria (15) and 22 from other states visited by QuoCCA educators (8 in Tasmania, 6 in Australian Capital Territory, 6 in New South Wales and 2 in Northern Territory).…”
Section: Dovepressmentioning
confidence: 99%
“…14 They work in close collaboration with the tertiary children's hospital and train and mentor staff in their hospital and smaller regional hospitals, where a champion model may be useful. 15,16 Through the progressive QuoCCA projects since 2015, the aim has been to evaluate the effectiveness of education by assessing it at all levels using Kirkpatrick's Model 17 based on a project logic. 2,18 Outputs were measured from QuoCCA education reports around Australia.…”
mentioning
confidence: 99%